Cross-border versus cross-sector interconnectivity in renewable energy systems. (1st April 2017) - Thellufsen, Jakob Zinck; Lund, Henrik
Abstract: In the transition to renewable energy systems, fluctuating renewable energy, such as wind and solar power, plays a large and important role. This creates a challenge in terms of meeting demands, as the energy production fluctuates based on weather patterns. To utilise high amounts of fluctuating renewable energy, the energy system has to be more flexible in terms of decoupling demand and production. This paper investigates two potential ways to increase flexibility. The first is the interconnection between energy systems, for instance between two countries, labelled as cross-border interconnection, and the second is cross-sector interconnection, i.e., the integration between different parts of an energy system, for instance heat and electricity. This paper seeks to compare the types of interconnectivity and discuss to which extent they are mutually beneficial. To do this, the study investigates two energy systems that represent Northern and Southern Europe. Both systems go through three developmental steps that increase the cross-sector interconnectivity. At each developmental step an increasing level of transmission capacities is examined to identify the benefits of cross-border interconnectivity. The results show that while both measures increase the system utilisation of renewable energy and the system efficiency, the cross-sector interconnection gives the best system performance. To analyse the possible interaction between cross-sector and cross-border interconnectivity, two main aspects have to be clarified. The first part defines the approach and the second is the construction of the two archetypes. Highlights: A method to investigate system integration and system interconnection is suggested. The implementation is investigated across a Northern and Southern energy system. The study identifies benefits of system integration and system interconnection. The performance of the energy system benefits most from system integration.